Readiness Analysis of Facility, Human Resources, and Marketing Strategies on The Increase in Medical Tourism Visits at BIMC Hospital Nusa Dua Bali - Ribut Agung Nugroho; Muhammad Anas; Mochamad Mochklas (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The trend of medical tourism visits in various countries continues to increase. The high increase in medical tourism services must be accompanied by hospitals' readiness to maintain quality and patient loyalty. This study aims to analyse the readiness of facilities, human resources, and marketing strategies for increasing medical tourism visits at BIMC Hospital Nusa Dua. This study is a case study with qualitative data collection thru in-depth interviews and direct observation. The results of this study indicate that BIMC Hospital Nusa Dua has prepared facilities to increase medical tourism service visits by adding the number of operating room procedures and treatments, as well as some modern medical equipment. In addition, the hospital has also prepared transportation and accommodation in collaboration with travel agents. Human resource readiness can be seen by providing overseas training for doctors to improve their competence. In addition, nursing staff and other personnel have been given both internal and external training. Excellent service training is provided to all staff to deliver outstanding service to customers. The marketing strategy focuses on improving product/service quality, implementing competitive pricing, accessibility, and promoting thru websites and social media. Conclusion: The increase in medical tourism visits is a significant concern, as evidenced by the development of hospital facilities, improved human resource competency, and effective marketing strategies to maintain service quality and patient loyalty. Keywords: Medical Tourism, Facility Readiness, Human Resources, Marketing Strategy.